UMPs deer conceived the second fawn - UMP, PNC (2020)
The deer, known as Pekan and Chini, raised in Mini Deer Park on the campus of Universiti Malaysia Pahang (UMP) in Pekan conceived their second fawn on April 22, 2020, at 7.00 am weighing 7kg after the birth of their first fawn in June last year.